DETERMINANTS OF PREGNANCY LOSS AMONG WOMEN OF REPRODUCTIVE AGE IN INDONESIA: Determinan Kehilangan Kehamilan Pada Wanita Usia Reproduksi di Indonesia - Arif Musoddaq, Muhamad; Hidayat, Taufiq; Riyanto, Slamet; Dyah Kusumawardani, Hastin; Kristanto Mulyantoro, Donny; Supadmi, Sri (Jurnal Berkala Epidemiologi, 2024)
Background. Both miscarriage and stillbirth occur in almost 20% of clinical pregnancies, resulting in pregnancy loss. The incidence has been associated with several risk factors and events of maternal adverse health outcomes. Purpose. This study was conducted to analyze some associated factors of pregnancy loss in Indonesia. Methods. This cross-sectional study used the 2017 Indonesia DHS data involving 18,882 female participants aged 15–49 years who had ever had a gestation. Pregnancy loss was the dependent variable, whereas the independent variables included education, employment, wealth status, advanced maternal age, grand multiparity, and cigarette smokers. Finally, the author used binary logistic regression to calculate the determinants. Results. The adjusted risk of pregnancy loss was significantly higher in respondents with lower education levels (AOR=1.25; 95% CI: 1.11-1.41) and employed (AOR=1.19; 95% CI: 1.10-1.29). The lower the wealth status of women, the higher the chance of pregnancy loss. The adjusted risk of pregnancy loss was higher in women of advanced maternal age (AOR=2.03; 95% CI: 1.37-3.02), those with grand multiparity (AOR=1.91; 95% CI: 1.74-2.09), and those who cigarette smokers (AOR=1.53; 95% CI: 1.25-1.87). Conclusion. The study concluded that six variables i.e., education, employment, wealth status, advanced maternal age, grand multiparity, and cigarette smokers are strong predictors of pregnancy loss in Indonesian women. Therefore, the government should make a policy to address the determinants of the pregnancy issue.